2020
DOI: 10.1101/2020.08.05.238857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Musculoskeletal Model Personalization Affects Metabolic Cost Estimates for Walking

Abstract: Assessment of metabolic energy cost as a metric for human performance has expanded across various fields within the scientific, clinical, and engineering communities. As an alternative to measuring metabolic cost experimentally, musculoskeletal models incorporating metabolic cost models have been developed. However, to utilize these models for practical applications, the accuracy of their metabolic cost predictions requires improvement. Previous studies have reported the benefits of using personalized musculos… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…studies have identified sensitivities to muscle parameters in both metabolic cost estimates of poststroke gait [75] and contact forces in the knee of an amputee walking with a prosthesis [76]. An additional source of further work for our framework will be to investigate the potential of musculoskeletal model calibration techniques [77] in combination with alternative objective functions, with the aim to recruit patients with gait pathologies.…”
Section: B Simulated Metabolic Costmentioning
confidence: 99%
“…studies have identified sensitivities to muscle parameters in both metabolic cost estimates of poststroke gait [75] and contact forces in the knee of an amputee walking with a prosthesis [76]. An additional source of further work for our framework will be to investigate the potential of musculoskeletal model calibration techniques [77] in combination with alternative objective functions, with the aim to recruit patients with gait pathologies.…”
Section: B Simulated Metabolic Costmentioning
confidence: 99%
“…Metabolic cost is defined as the energy consumed by the body during a given activity, in this case, a single walking cycle. Based on a previous study (Arones et al, 2020), we used Bhargava's model to calculate the metabolic cost (Bhargava et al, 2004). Stride length is defined as the distance between two consecutive heel strikes of the same foot.…”
Section: Gluteus Minimus (Posterior)mentioning
confidence: 99%